Geochemical Study of the Itabirite Iron Ores of the Alegria Mine - Quadrilátero Ferrífero, Minas Gerais, Brazil - Veríssimo, C. U V; Schrank, A.; Pires, F. R M; Hasui, Y. [UNESP]; Zanardo, A. [UNESP]; Parente, C. V. (My University, 2002)
The iron ores of Alegria mine are composed of itabirites enclosing minor bodies of high-grade ores. The itabirites are classified according to mineralogical composition in five types: martite-rich, goethite-rich, specularite-rich, magnetite-rich and anphibolite-rich ores. The hematites are martite-rich, magnetite-rich, specularite-rich and more rarely, amphibolite-rich. Other classification criteria of the ores are based on the physical properties and the degree of compaction. As such, the itabirites and hematites can be classified as hard, friable and soft types. The mineralogical/textural evolution of the ores is linked to the pressure and temperature conditions that accompanied the tectonic processes in anphibolite facies and the different degrees of subsequent surficial weathering processes. Petrographic and microstructural studies indicate that the magnetite and amphibole bearing itabirites represent the parent rocks that created the other itabirites and that the specularite itabirites and the hard martite types are related to silica dissolution and redeposition in zones of high and low strain. Most of itabirites ores correspond to chert oxide facies banded iron formation, except the goethite and amphibole bearing itabirite that resemble a silicate or oxide-silicate facies with minor carbonate impurities. The great mass and pods of soft martite itabirites are probably shaley oxide facies BIFs with little volcanic contribution. Trace element contents of the Alegria's itabirites show strong dissimilarities with BIFs associated with volcanism (Algoma type), but closely ressemble to the Lake Superior type, with high content in Cr, Co and low V, Ni, Cu and Zn. Although the absolute contents of REE present in the Alegria's itabirites are, in general very low, the pattern when normalised by NASC is similar to the great majority of the Archean and Paleoproterozoic BIFs elsewhere in the world, and characterised by positive Eu anomaly.